PERCEPÇÃO DA QUALIDADE NA PRESTAÇÃO DE SERVIÇOS MÉDICO-HOSPITALARES NA MATERNIDADE DA SANTA CASA DE MISERICÓRDIA DE JUIZ DE FORA: UM PARALELO ENTRE A VISÃO DO CLIENTE E A DOS PROFISSIONAIS DE SAÚDE - Mendonça, José Geraldo de (2010)
Hospitals, especially the maternity wards, have been investing in modernization and quality care services as their competitive edge, mainly due to the pressure from the increasing number of competitors in the area. Bearing this in mind, this study is aimed at identifying how users/clients and health care professionals from the maternity ward of the Santa Casa de Misericórdia de Juiz de Fora perceive such quality. These results can enable the management of the hospital in making decisions on the quality policies to be adopted as they provide clues on the perception and expectations from both professionals and users/clients. In order to achieve this goal, the health quality approaches by DONABEDIAN (1980) are emphasized, as well as the analyses and services by ZARIFAN (2001, 2003) and SALERMO (2001), in the light of the humanization program recently implemented by the hospital. Its contribution to the quality health care services is also discussed. This is an exploratory study which uses methodology influenced by approaches that contribute for greater similarity to real work (GUÉRIN, et al., 2001). It prioritizes the professionals´ experience on the one hand and the users´ on the other hand. It also uses indirect methods such as interactions, questionnaires, open ended observation and group discussion, which aim to identify the gap between what is prescribed (theplanning and conception) and what is effectively carried out (the real action). After analyzing and comparing the two views selected for the study, both convergent and divergent aspects were found. The former refer to humanization in care services, technical expertise and the view of hospitality as weaknesses. The latter refer to visiting hours, swift assistance, sticking to schedules, hygiene and safety.